Implementation of Lecturer Competency Development in Higher Education (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to describe the planning of lecturer competency development, organization of lecturer competency development, implementation of lecturer competency development, supervision of lecturer competency development, evaluation of lecturer competency development at the Syekh Abdul Halim Hasan Binjai Institute.Methodology: This research method is a qualitative research method with a phenomenological research approach. This research was conducted to build knowledge through understanding and discovery based on a methodology that investigates a phenomenon and problem. Data collection techniques used are observation, interviews, documentation studies. Data management consists of data reduction, data display/data presentation, data analysis, drawing conclusions for research results.Main Findings: The findings reveal that while the institute demonstrates strong commitment to improving teaching quality, several issues persist, such as limited resources, insufficient integration of technology, and supervision focused mainly on administrative compliance rather than pedagogical enhancement. The evaluation process also tends to emphasize attendance and reporting rather than measurable improvement in teaching skills or student outcomes. The study highlights the need for a more reflective and data-driven approach to faculty development, emphasizing participatory planning, effective feedback mechanisms, and the establishment of long-term evaluation systems.Novelty/Originality of this study: The novelty of this research lies in its holistic assessment of lecturer competency development within an Islamic higher education context, bridging managerial and pedagogical dimensions. The implications extend to policy and practice in higher education, suggesting that competency development must transition from procedural routines to transformative learning experiences.
Keywords: Competency Development; Higher Education; Implementation; Lecturer